Glacially induced faulting along the NW segment of the Sorgenfrei-Tornquist Zone, northern Denmark: Implications for neotectonics and Lateglacial fault-bound basin formation - Brandes, Christian; Steffen, Holger; Sandersen, Peter B.E.; Wu, Patrick; Winsemann, Jutta (Amsterdam : Elsevier B.V., 2018)
The Sorgenfrei-Tornquist Zone (STZ) is the northwestern segment of the Tornquist Zone and extends from Bornholm across the Baltic Sea and northern Denmark into the North Sea. It represents a major lithospheric structure with a significant increase in lithosphere thickness from south to north. A series of meter-scale normal faults and soft-sediment deformation structures (SSDS) are developed in Lateglacial marine and lacustrine sediments, which are exposed along the Lønstrup Klint cliff at the North Sea coast of northern Denmark. These deformed deposits occur in the local Nørre Lyngby basin that forms part of the STZ. Most of the SSDS are postdepositional, implying major tectonic activity between the Allerød and Younger Dryas (∼14 ka to 12 ka). The occurrence of some syn- and metadepositional SSDS point to an onset of tectonic activity at around 14.5 ka. The formation of normal faults is probably the effect of neotectonic movements along the Børglum fault, which represents the northern boundary fault of the STZ in the study area. The narrow and elongated Nørre Lyngby basin can be interpreted as a strike-slip basin that developed due to right-lateral movements at the Børglum fault. As indicated by the SSDS, these movements were most likely accompanied by earthquake(s). Based on the association of SSDS these earthquake(s) had magnitudes of at least Ms ≥ 4.2 or even up to magnitude ∼ 7 as indicated by a fault with 3 m displacement. The outcrop data are supported by a topographic analysis of the terrain that points to a strong impact from the fault activity on the topography, characterized by a highly regular erosional pattern, the evolution of fault-parallel sag ponds and a potential fault scarp with a height of 1–2 m. With finite-element simulations, we test the impact of Late Pleistocene (Weichselian) glaciation-induced Coulomb stress change on the reactivation potential of the Børglum fault. The numerical simulations of deglaciation-related lithospheric stress build-up additionally support that this neotectonic activity occurred between ∼14.5 and 12 ka and was controlled by stress changes that were induced by the decay of the Scandinavian ice sheet. In the Holocene, the stress field in the study area thus changed from GIA-controlled to a stress field that is determined by plate tectonic forces. Comparable observations were described from the central STZ in the Kattegat area and the southeastern end of the STZ near Bornholm. We therefore interpret the entire STZ as a structure where glacially induced faulting very likely occurred in Lateglacial times. The fault reactivation was associated with the formation of small fault-bound basins that provided accommodation space for Lateglacial to Holocene marine and freshwater sediments. © 2018 The Authors